Deep phenotyping of facioscapulohumeral muscular dystrophy type 2 by magnetic resonance imaging. (14th August 2020) - Giacomucci, G.; Monforte, M.; Diaz‐Manera, J.; Mul, K.; Fernandez Torrón, R.; Maggi, L.; Marini Bettolo, C.; Dahlqvist, J. R.; Haberlova, J.; Camaño, P.; Gros, M.; Tartaglione, T.; et al.
Abstract : Background and purpose: The aim was to define the radiological picture of facioscapulohumeral muscular dystrophy 2 (FSHD2) in comparison with FSHD1 and to explore correlations between imaging and clinical/molecular data. Methods: Upper girdle and/or lower limb muscle magnetic resonance imaging scans of 34 molecularly confirmed FSHD2 patients from nine European neuromuscular centres were analysed. T1‐weighted and short‐tau inversion recovery (STIR) sequences were used to evaluate the global pattern and to assess the extent of fatty replacement and muscle oedema. Results: The most frequently affected muscles were obliquus and transversus abdominis, semimembranosus, soleus and gluteus minimus in the lower limbs; trapezius, serratus anterior, latissimus dorsi and pectoralis major in the upper girdle. Iliopsoas, popliteus, obturator internus and tibialis posterior in the lower limbs and subscapularis, spinati, sternocleidomastoid and levator scapulae in the upper girdle were the most spared. Asymmetry and STIR hyperintensities were consistent features. The pattern of muscle involvement was similar to that of FSHD1, and the combined involvement of trapezius, abdominal and hamstring muscles, together with complete sparing of iliopsoas and subscapularis, was detected in 91% of patients. Peculiar differences were identified in a rostro‐caudal gradient, a predominant involvement of lower limb muscles compared to the upper girdle, and in the higher percentage of STIR hyperintensities in FSHD2. Conclusion: This multicentre study defines the pattern of muscle involvement in FSHD2, providing useful information for diagnostics and clinical trial design. Both similarities and differences between FSHD1 and FSHD2 were detected, which is also relevant to better understand the pathogenic mechanisms underlying the FSHD‐related disease spectrum.